Blending Fe3O4 into a Ni/NiO composite for efficient and stable bifunctional electrocatalyst. (20th February 2018) - Xie, Yiming; Wang, Xianfu; Tang, Kai; Li, Qun; Yan, Chenglin
Abstract: As a promising strategy for clean energy production, electrochemical water splitting requires high-efficient, well-stable, and earth-abundant electrocatalysts to realize its practical application. Herein, we report a heterogeneous Fe3 O4 -blended Ni/NiO composite fabricated through a salt-template method as highly active bifunctional catalysts for both oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). To reach a current density of 10 mA cm −2, the Ni/NiO/Fe3 O4 requires low overpotential of 258 mV for OER in alkaline media and 206 mV for HER in acidic media, respectively, much lower than those of Ni/NiO, Fe3 O4 and other Ni-based oxides. The excellent electrocatalytic performance can be ascribed to the enhanced charge-transfer kinetics between Ni and Fe sites and improved active sites resulted from the large nano-interface between Ni compounds and Fe3 O4 . This work provides a new method to design high-performance non-noble metal Ni-based electrocatalysts by incorporating Fe-doping and nano-interface-fabrication together, which can also be applied to develop other novel hybrid electrocatalysts for practical application.